Spn1 Regulates the GNBP3-Dependent Toll Signaling Pathway in Drosophila melanogaster. - Fullaondo, A.; García-Sánchez, S.; Sanz-Parra, A.; Recio, E.; Lee, S.Y.; Gubb, D. (Molecular and Cellular Biology, 2011)
The Drosophila genome encodes 29 serpins, most of unknown function. We show here that Spn1 is an active protease inhibitor of the serpin superfamily. Spn1 inhibits trypsin in vitro and regulates the Toll-mediated immune response in vivo. Expression of the Toll-dependent transcripts Drosomycin and IM1 is increased in Spn1 null mutants. Overexpression of Spn1 reduces the induction of Drosomycin upon immune challenge with fungi but not Gram-positive bacteria. Similar reductions in Drosomycin levels are observed in the psh, spz, and grass mutants of the Toll signaling pathway. These results support a role of Spn1 as a repressor of Toll activation upon fungal infection. Epistatic analysis places Spn1 upstream of Spätzle processing enzyme and Grass, in the fungal cell wall-activated side branch of the pathway. Overexpression of the pattern recognition receptor GNBP3 activates the ?-1,3-glucan-sensitive side branch of the Toll pathway. The resultant increased Drosomycin level is reduced by concomitant overexpression of Spn1, confirming that Spn1 regulates the fungal cell wall side branch. Spn1 null mutants show altered susceptibility to fungal infection compared to the wild type, demonstrating a requirement for Spn1 in the fine regulation of the immune response.